Commentary on Ohriner (2016) - Condit-Schultz, Nathaniel (Empirical Musicology Review, 2017)
This commentary offers a review of Ohriner's corpus-based research on rap music, and includes an in-depth comparison of Ohriner's model with my own. It highlights multiple divergences in our underlying methodologies, and outlines the potential impact of such differences on the research results. Ohriner provides a convincing and widely appealing presentation of how musical corpora may be leveraged to effectively enhance traditional forms of analysis. However, I question his approach to certain processes, such as sampling, transcription, and segmentation. I believe that his analysis would benefit from stronger definitions in these areas.